Burrow usage patterns and decision-making in meerkat groups. (6th November 2019) - Strandburg-Peshkin, Ariana; Clutton-Brock, Tim; Manser, Marta B
Abstract: Choosing suitable sleeping sites is a common challenge faced by animals across a range of taxa, with important implications for the space usage patterns of individuals, groups, and ultimately populations. A range of factors may affect these decisions, including access to resources nearby, shelter from the elements, safety from predators, territorial defense, and protection of offspring. We investigated the factors driving patterns of sleeping site use in wild Kalahari meerkats ( Suricata suricatta ), a cooperatively breeding, territorial mongoose species that forages on scattered resources and makes use of multiple sleeping sites (burrows). We found that meerkat groups used some burrows much more often than others. In particular, large burrows near the center of the territory were used more often than small and peripheral burrows, and groups became even more biased toward central burrows when rearing pups. Meerkats also used their sleeping burrows in a nonrandom order. When they changed sleeping burrows, they moved disproportionately to nearby burrows but did not always select the closest burrow. Burrow decisions also reflected responses to short-term conditions: rates of switching burrows increased after encounters with predators and when resources were depleted, whereas group splits were associated with a reduced probability of switching. The group's dominant female appeared to have disproportionate influence over burrow decisions, as groups were more likely to switch burrows when her foraging success was low. Our results link behavioral and movement ecology to show that a multitude of environmental and social factors shape daily group decisions of where to spend the night. Abstract : Everyone has to rest sometimes—but where? Meerkats prefer large sleeping burrows near the center of their ranges and are more selective when rearing pups. They respond to short-term conditions (such as predators and resource depletion) by becoming more likely to switch burrows. The group's dominant female seems to exert an outsized influence over these decisions. Understanding daily decisions of this kind thus provides insights into the social, spatial, and ecological factors underlying group decision-making.